PROBLEMATIKA PEMILIHAN WALI KOTA MAKASSAR DITENGAH PANDEMI COVID-19 DALAM PERSPEKTIF MAQASHID Al-SYARIAH - Adriyan Putra Ramdah; St. Halimang (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
The rescheduling of the simultaneous regional elections in December 2020 reaped pros and cons, even considered unrealistic as positive cases of Covid-19 surged. This study aims to find out the problems of the implementation of the Makassar Mayoral Election in the midst of the Covid-19 pandemic. This research uses qualitative field methods with empirical juridical approach and syar'i approach. The results of this study show that the Mayoral Election, which was held amid the soaring number of positive cases of Covid-19, is a policy that can threaten mutual safety. Although the change of leadership is a constitutional mandate, but with a health emergency the implementation may be postponed. In the concept of al-maqasid al-sharia, keeping the soul is second only to the obligation to maintain religion, and the concept is in line with the state objectives that have been affirmed in the Basic Law.